2021
DOI: 10.3389/fpsyt.2021.641549
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis, Impaired Driving, and Road Safety: An Overview of Key Questions and Issues

Abstract: The road safety impact of cannabis has been a topic of much discussion and debate over the years. These discussions have been revitalized in recent years by initiatives in several jurisdictions to legalize non-medical cannabis. Canada became the second country to legalize non-medical cannabis use in October, 2018, preceded by Uruguay in December 2013. Road safety concerns were key issues in the Canadian government's deliberations on the issue. In this paper, we identify several key questions related to the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…This echoes work by Gibson et al 55 who conducted a qualitative study on perceptions of alcohol and cannabis use among male Canadian veterans with PTSD ( N = 5) and observed that participants hesitated to use cannabis, even when medically prescribed, because they were concerned about how they may be perceived by their peers and society at large. As observed by Compton et al 63 stereotypes and biases about cannabis users continue to persist despite a general increase in the acceptability of cannabis use within society. It is common for veterans to experience self-stigma around cannabis use, 35 owing in part to deeply ingrained institutional military regulations and values prohibiting cannabis use.…”
Section: Discussionmentioning
confidence: 93%
“…This echoes work by Gibson et al 55 who conducted a qualitative study on perceptions of alcohol and cannabis use among male Canadian veterans with PTSD ( N = 5) and observed that participants hesitated to use cannabis, even when medically prescribed, because they were concerned about how they may be perceived by their peers and society at large. As observed by Compton et al 63 stereotypes and biases about cannabis users continue to persist despite a general increase in the acceptability of cannabis use within society. It is common for veterans to experience self-stigma around cannabis use, 35 owing in part to deeply ingrained institutional military regulations and values prohibiting cannabis use.…”
Section: Discussionmentioning
confidence: 93%
“…Alternatively, the sample size in the present study was relatively small (Brands et al 2019, Marcotte et al 2022, but not unprecedented (Bosker et al 2012), and a lack of effect on other measures may reflect a lack of statistical power. Finally, this is the first study of edible cannabis on a driving simulator and it is possible that edibles have a different impact on driving than that following the smoked or vaped route, upon which current knowledge rests (Simmons et al 2022, Alvarez et al 2021, Brands et al 2021. Future converging evidence from emerging investigations will help to determine the impact of cannabis edibles on driving.…”
Section: Recreational 19mentioning
confidence: 90%
“…The results of driving simulator studies suggest that there is a dose-dependent alterations in driving (Ronen et al 2008, Hartman et al 2016 after cannabis, suggesting a relationship to blood THC. Studies so far have found increased 'weaving' (standard deviation of lateral position; SDLP) (Veldstra et al 2015, Ronen et al 2008, Hartman et al 2016, Bosker et al 2012, Simmons et al 2022, Arkell et al 2019, Arkell et al 2020, Alvarez et al 2021, Brands et al 2021) and changes in both speed (Ronen et al 2008, Hartman et al 2016, Simmons et al 2022, Alvarez et al 2021, Brands et al 2021, Di Ciano et al 2020, Brands et al 2019, Lenne et al 2010) and reaction time (Alvarez et al 2021, Brands et al 2021, Lenne et al 2010, Sewell et al 2009, Hartley et al 2019) following smoked cannabis. Important questions thus remain as to the impact of cannabis edibles on driving.…”
Section: Introductionmentioning
confidence: 99%
“…The main psychoactive component of marijuana, active Delta-9-tetrahydrocannabinol (THC), had a significantly higher prevalence among seriously or fatally injured road users involved in motor vehicle collisions who presented at five US high-flow level 1 trauma centers and medical examiners during the pandemic compared to pre-COVID-19, and it was more prevalent among those road users during the COVID-19 pandemic compared to alcohol ( 34 ). Although research has shown that marijuana use impairs driving performance, including cognition, attention, reaction time, and vigilance ( 35 ), the effects of marijuana on driving performance are not predictable due to different individual characteristics (i.e., tolerance, frequent vs. occasional users) ( 36 , 37 ) and marijuana itself (i.e., dosage, administration route) ( 37 ). Additionally, in contrast to alcohol, which is more easily excreted from the body and has known limits for impairment, we have yet to determine a gold-standard for driving impairment following marijuana use and is still detectable in body fluids long after impairment has stopped ( 31 , 38 ).…”
Section: Discussionmentioning
confidence: 99%